Anatomic and magnetic resonance imaging features of the salivary glands in the dog. (14th August 2018) - Gil, Francisco; Arencibia, Alberto; García, Verónica; Ramírez, Gregorio; Vázquez, José María
Abstract: The aim of the study was to describe the anatomical location and the topographic relationship of the major salivary glands to associated tissues in six dog cadavers by high‐field magnetic resonance imaging (MRI) and gross anatomical dissections and sections. Spin‐echo T1‐weighted and T2‐weighted magnetic resonance (MR) images were obtained in transverse, sagittal, and dorsal planes with a 1.5 T magnet. The digastric muscle, the external auditory canal, the eyeball, and the medial pterygoid muscle were the most consistent topographic landmarks for the identification of the mandibular, parotid, and zygomatic salivary glands, respectively. The best differentiation and contrast of the glands was observed in the T2‐weighted images. In contrast with the osseous and muscular tissues, the salivary glands appeared hyperintense in greater or lesser measure except for the parotid gland, which displayed a hypointense signal. The rostral part of the monostomatic sublingual gland was precisely located between the tongue and the mylohyoid muscle. The best delineation between the caudal part of the monostomatic sublingual gland and the cranial aspect of the mandibular gland was observed in dorsal MRI at the level of the palate and the branches of the superior dental arcade. Good evaluation of the mandibular, parotid, caudal part of the monostomatic sublingual, zygomatic and buccal ventral glands was possible in sagittal MRI in close relation with the external auditory canal and the temporomandibular joint. The ventral buccal glands were also observed near the buccal vestibule as was the palatine glands within the soft palate.